The Relationship Between Inflammation and Impaired Wound Healing in a Diabetic Rat Burn Model. Issue 2 (March 2016) - Tian, Ming; Qing, Chun; Niu, Yiwen; Dong, Jiaoyun; Cao, Xiaozan; Song, Fei; Ji, Xiaoyun; Lu, Shuliang
Abstract : Inflammation, initiated by polymorphonuclear neutrophil (PMNs) infiltration, is the first step in wound healing. The aim of this study is to investigate the function of neutrophils in a diabetes-impaired wound healing model and to explore the underlying mechanisms leading to neutrophil dysfunction. Superficial second-degree burns were created in the streptozotocin (STZ)-induced diabetic rat model, and the changes in the levels of advanced glycation end products (AGE), receptor of AGE (RAGE), inflammatory cytokines and oxidative markers, as well as cell apoptosis were determined. The effects of AGE on isolated PMNs were also determined in vitro. We found that deposition of AGE in diabetic rat skin activated the neutrophils before injury. However, the dense inflammatory band failed to form in the diabetic rats after injury. Compared with the controls, enhanced expression of RAGE and accelerated cell apoptosis were observed in the burned skin of diabetic rats. The altered expression pattern of inflammatory cytokines (tumor necrosis factor-alpha and interleukin-8) and oxidative markers (glutathione peroxidase, myeloperoxidase, hydrogen peroxide, and malondialdehyde) between burned skin of diabetic and control rats revealed delayed neutrophil chemotaxis and respiratory burst. Furthermore, the results in vitro showed that exposure to AGE inhibited the viability of PMNs, promoted RAGE production and cell apoptosis, and prevented the migration of PMNs, consistent with the findings in vivo. Besides, AGE-treated neutrophils showed increased secretion of inflammatory cytokines and increased oxidative stress. Combined, our results suggest that an interaction between AGE and its receptors inhibits neutrophil viability and function in the diabetic rat burn model.